2022
DOI: 10.3390/jcm11216586
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Fear and Anxiety among Patients with Chronic Heart Failure: A Cross Sectional Study

Abstract: Although the current management of COVID-19 is mainly focused on efficacious vaccine and infection control, the most common psychological reactions (such as fear and anxiety) associated with the COVID-19 pandemic have not been investigated and even neglected in patients with heart failure who are at greater risk for morbidity and mortality. We assessed COVID-19 related fear and anxiety among patients with heart failure and determined their associated factors. A cross sectional survey was conducted among 300 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Another study reported that a history of regular hospital visits was a significant risk factor for psychological distress in the general population during the Covid-19 pandemic [39]. The high prevalence of psychological distress in people with chronic diseases may be related to the fear of a high mortality rate due to Covid-19 in this group of the population [40]. Nagasu et al (2021) reported that people with low income perceived more psychological distress than other groups [34].…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that a history of regular hospital visits was a significant risk factor for psychological distress in the general population during the Covid-19 pandemic [39]. The high prevalence of psychological distress in people with chronic diseases may be related to the fear of a high mortality rate due to Covid-19 in this group of the population [40]. Nagasu et al (2021) reported that people with low income perceived more psychological distress than other groups [34].…”
Section: Discussionmentioning
confidence: 99%
“…Recognizing the impact of social isolation and the stress of the pandemic on the mental health of patients and staff also underscores the need for comprehensive psychological support measures in stroke care strategies 119 . To address COVID-19-related fears, stroke care must include the integration of psychological support, particularly emphasizing the consideration of physiological risk factors linked to COVID-19 comorbidities 115 . For future preparedness, a holistic approach that encompasses technological advancements, public education, and mental health support will be essential to ensure optimal patient outcomes and maintain the integrity of stroke care systems during crises.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has indicated that the successful implementation of performance improvement programs and robust stroke care systems can help maintain high-quality care during health emergencies 114 . Additionally, mitigating delays and preventing reluctance to seek medical care requires addressing various factors such as overcoming fear of COVID-19 infection 115 ; managing transportation restrictions (i.e., many individuals indicated being ensure whether travel to hospital was permitted and feared exposing patients to COVID-19 116 ), and alleviating burdens on the healthcare system. Notably, innovations have been proposed to alleviate these burdens and safeguard stroke survivors during crises, including: (1) implementing teleneurology networks to enhance thrombolysis access for acute ischemic stroke; (2) enhancing the efficiency of emergency care for acute ischemic stroke (e.g., by preregistering patients during transport via ambulance and having the neurologist obtain clinical history electronically prior to arrival at the hospital); and (3) offering alternatives to inpatient care for transient ischemic attacks through an accelerated diagnostic protocol in the observation unit 117 .…”
Section: Discussionmentioning
confidence: 99%
“…Severe psychological and emotional stress will seriously increase the likelihood of COVID-19 infection [ 11 ]. Stress among residents with the history of chronic disease and allergic was higher than among residents without chronic diseases, possibly because residents with the history of chronic diseases and allergic were more likely to be infected with the COVID-19 virus [ 46 , 47 ] and had a higher level of fear of COVID-19 virus [ 48 ], resulting in a significant increase in stress among these residents.…”
Section: Discussionmentioning
confidence: 99%